2001
DOI: 10.1007/s004250100534
|View full text |Cite
|
Sign up to set email alerts
|

The CO 2 -concentrating mechanism in the physiological context: lowering the CO 2 supply diminishes culture growth and economises starch utilisation in Chlamydomonas reinhardtii

Abstract: In a synchronously grown Chlamydomonas reinhardtii (Chlorophyceae) culture the CO2-concentrating mechanism (CCM) was induced by lowering the CO2 level from 4% to 0.036% CO2 (culture HL). The effects of the reduced carbon supply on starch levels were studied over a period of up to 100 h and compared with control cultures kept either at 4% CO2 (culture H) or continuously at ambient air (0.036% CO2, culture L). Lowering the CO2 supply reduced culture growth as estimated by chlorophyll, protein and cell density. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The same argument may be used to explain the increase in free bases (A,U, and G) and guanosine/uridine by RNA degradation. There are very significant interactions between CO 2 availability and nitrogen availability on the expression of the CCM in C. reinhardtii (Giordano et al, 2003), and interactions between carbon and nitrogen metabolism with changing CO 2 supply are to be expected (Thyssen et al, 2001). There seems to be no information on the effects of growth at different CO 2 concentrations on the carbon-nitrogen ratio of C. reinhardtii, and data for other algae show that an increased carbon-nitrogen ratio in microalgal cells grown at high CO 2 does occur but is by no means universal (Beardall et al, 2005b;Finkel et al, 2010).…”
Section: Focus On Differences 3 H After Ccm Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same argument may be used to explain the increase in free bases (A,U, and G) and guanosine/uridine by RNA degradation. There are very significant interactions between CO 2 availability and nitrogen availability on the expression of the CCM in C. reinhardtii (Giordano et al, 2003), and interactions between carbon and nitrogen metabolism with changing CO 2 supply are to be expected (Thyssen et al, 2001). There seems to be no information on the effects of growth at different CO 2 concentrations on the carbon-nitrogen ratio of C. reinhardtii, and data for other algae show that an increased carbon-nitrogen ratio in microalgal cells grown at high CO 2 does occur but is by no means universal (Beardall et al, 2005b;Finkel et al, 2010).…”
Section: Focus On Differences 3 H After Ccm Inductionmentioning
confidence: 99%
“…Rearrangement of starch from granules to the pyrenoid sheath is characteristic for the early part of the low-CO 2 acclimation response (Thyssen et al, 2001). The absolute level of starch synthesis is lower in low-CO 2 cells, although it represents a larger fraction of the total carbon fixed.…”
Section: Focus On Differences 3 H After Ccm Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of circadian clock regulation of starch metabolism in vascular plants is discussed. It has been previously noted that photoautotrophic cultures of C. reinhardtii grown either in low or high CO 2 displayed a diurnal rhythm of starch content that did not correlate with lights off and on (Klein, 1987;Thyssen et al, 2001). Because the minimal starch content is reached at the middle of the light phase, we investigated the possibility that starch metabolism as a whole (as reflected by starch content) could be under tight circadian clock control in the monocellular alga C. reinhardtii.…”
mentioning
confidence: 98%
“…Similarly, the activities of carbonic anhydrase and nitrate reductase enzymes in C. pyrenoidosa and Chlamydomonas reinhardtii exhibited different responses to elevation of dissolved CO2 content (Xia and Gao 2005). Moreover, other studies demonstrated that increasing CO2 content from ambient to 2-5% improves biomass growth but has either negative (up to 2-3 fold reduction) or no effect on starch accumulation when applied without the cell arrest (Thyssen et al 2001;Izumo et al 2007;Li et al 2013). Lowering CO2 concentration can induce carbon dioxide concentrating mechanisms (CCM) that may enhance CO2 supply to ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO), and thus improve photosynthesis efficiency and carbon storage (Raven 2010).…”
Section: Inorganic and Organic Carbonmentioning
confidence: 97%